Case report: Pediatric anti-gamma aminobutyric acid-B receptor encephalitis with benign prognosis - Wang, Yeping; Ren, Xiaoyan; Shen, Yu; Hua, Yi; Xu, Lu; Zhang, Weiran; Sheng, Guoxia; Jiang, Peifang; Yuan, Zhefeng; Liu, Liu; Gao, Feng (Frontiers in Pediatrics, 2023)
Objective To explore the clinical characteristics of pediatric anti-gamma-aminobutyric acid-B receptor (GABABR) encephalitis to enhance the understanding and improve the diagnostic and therapeutic strategies for this disease. Methods We report a rare case of a female pediatric patient with anti-GABABR encephalitis who was treated at the Children's Hospital of Zhejiang University School of Medicine. Literature search was performed to explore the clinical characteristics of pediatric anti-GABABR encephalitis. Results The patient exhibited recurrent epileptic seizure, status epilepticus, and psychiatric symptoms at the age of 11 years and 10 months. Anti-GABABR antibodies were positive in cerebrospinal fluid and serum. Brain magnetic resonance imaging (MRI) exhibited abnormal signals in the left hippocampus. Symptoms and abnormality of brain MRI were improved after administration of immunosuppressants, anti-seizure and antipsychotic drugs. Two of pediatric anti-GABABR encephalitis with clinical data were identified through literature search. Analysis of these three cases suggested that the pediatric patients primarily experienced limbic encephalitis, with no tumor incidence. A favorable immunotherapy response was demonstrated with a superior prognosis in all the cases. Conclusions We reported a pediatric anti-GABABR encephalitis case with early age of onset. Promt autoimmune antibody testing and tumor screening, as well as immunomodulatory treatment immediately after a definitive diagnosis are warranted to improve prognosis.